Profiling fatal and serious injury crashes in South Australia according to the Swedish transport administration model. (10th March 2022) - Baldock, Matthew; Stokes, Christopher; Mongiardini, Mario
Abstract: Objectives: This article describes a study examining fatal road crashes in South Australia (SA) according to the safety model developed by the Swedish Road Administration (STA). The STA model is based on the biomechanical limits that human beings can tolerate and specifies a number of elements that must be present for "compliance" with the model: driving at or below the speed limit, driver not intoxicated by alcohol or drugs, vehicle occupants wearing a seatbelt, car with a EuroNCAP rating of 5 stars, car equipped with electronic stability control, and a road with an EuroRAP rating of 4 stars. Method: The study used a sample of 105 fatal crashes in SA in 2010 and 2011 and a comparison sample of 136 serious injury crashes from 2014 to 2017. Results: It was found that there were high levels of noncompliance with all elements of the STA model, with multiple forms of noncompliance in a clear majority of fatal cases. Conclusions: Considerable gains in safety could occur with greater penetration into the SA fleet of 5-star cars fitted with ESC and other vehicle safety technology, especially as the majority of both sets of crashes were of a type involving loss of vehicular control. It is also important to note that risky road user behavior was less common in the serious injury crashes and so a road safety strategy focusing on changing road user behavior will be ineffective for addressing the major factors contributing to non-fatal road trauma.